Hypoxia-induced metabolic reprogramming in mesenchymal stem cells: unlocking the regenerative potential of secreted factors - Jaraba-Álvarez, Wendy V.; Uscanga-Palomeque, Ashanti C.; Sanchez-Giraldo, Vanesa; Madrid, Claudia; Ortega-Arellano, Hector; Halpert, Karolynn; Quintero-Gil, Carolina (Frontiers in Cell and Developmental Biology, 2025)
Mesenchymal stem cells (MSCs) are a cornerstone of regenerative medicine, primarily due to their ability to secrete bioactive factors that modulate inflammation, promote tissue repair, and support regeneration. Recent research highlights the importance of preserving the native cellular microenvironment to optimize MSC function and survival post-transplantation. Preconditioning strategies, such as hypoxia exposure, have emerged as powerful tools to enhance MSC therapeutic potential by mimicking physiological conditions in their natural niche. This perspective article explores the metabolic adaptations induced by hypoxia in MSCs, focusing on shifts in mitochondrial function, glycolysis, oxidative phosphorylation, and metabolic intermediates that enhance cellular survival and bioactivity. We also discuss how these metabolic changes influence the composition and function of MSC-derived secreted factors, particularly exosomes and other extracellular vesicles, in modulating tissue repair. Furthermore, we provide an overview of preclinical and clinical studies that have evaluated hypoxia-preconditioned MSCs and their byproducts, assessing their efficacy in various therapeutic contexts. Special attention is given to the role of hypoxia-induced mitochondrial adaptations in improving MSC function and the emerging potential of metabolic inhibitors or respiration modulators as strategies to further refine MSC-based therapies. By integrating metabolic insights with clinical evidence, we aim to offer a comprehensive perspective on optimizing MSC culture conditions to enhance their regenerative properties, acknowledging that this remains a theoretical standpoint, as conventional culture methods are generally not conducted under hypoxic conditions. This approach holds promise for the development of more effective therapeutic strategies that leverage metabolic modulation to improve MSC-based interventions for a range of diseases.